Impact of cisplatin dose intensity on human papillomavirus-related and -unrelated locally advanced head and neck squamous cell carcinoma. (November 2016) - Spreafico, Anna; Huang, Shao Hui; Xu, Wei; Granata, Roberta; Liu, Chen-Shin; Waldron, John N.; Chen, Eric; Ringash, Jolie; Bayley, Andrew; Chan, Kelvin K.W.; Hope, Andrew J.; Cho, John; et al.
Abstract: Aim: The aim is to evaluate the impact of cisplatin dose modification on outcomes of human papillomavirus (HPV)-related (HPV+) and HPV-unrelated (HPV−) locally advanced head and neck cancer (LAHNC) treated with chemoradiotherapy (CRT). Patients and methods: A pooled analysis was conducted of stage III/IV oropharyngeal cancer (OPC), carcinoma of unknown primary (CUP) and laryngo-hypopharyngeal cancer (LHC) patients treated with single-agent cisplatin CRT in 2000–2012 from two tertiary academic cancer centres. HPV status was determined by p16 staining and/or in situ hybridisation. LHC was assumed to be HPV−. Unknown HPV status OPC/CUPs were excluded. Overall survival (OS) was calculated. Multivariable analysis (MVA) evaluated the impact of cisplatin dose intensity on survival for HPV+ and HPV− cohorts separately. Results: A total of 404 HPV+ and 255 HPV− LAHNC (481 OPC, 18 CUP, 160 LHC) patients were included. Median follow-up was 4.3 (0.5–11.9) years. Three-year OS for cisplatin <200, =200, and >200 mg/m 2 subgroups were 52%, 60%, and 72% ( P = 0.001) for the HPV− and 91%, 90%, and 91% ( P = 0.30) for the HPV+ patients. MVA confirmed a survival benefit with cisplatin >200 mg/m 2 for the HPV− (hazard ratio [HR] 0.5, 95% confidence interval [CI]: 0.3–0.7, P < 0.001) but not for HPV+ (HR 0.6, 95% CI: 0.4–1.1, P = 0.104). There was a superior OS trend in the HPV+ T4 or N3 high-risk subset ( N = 107) with cisplatin >200 mg/m 2 (HR 0.5, 95% CI: 0.2–1.1, P = 0.07). Conclusions: A survival benefit of cisplatin dose >200 mg/m 2 is evident for HPV− LAHNC patients, but not for HPV+ cohort overall, although the T4 or N3 subset may benefit from a higher cumulative cisplatin dose. Highlights: Cisplatin dose reduction has different survival impact for human papillomavirus (HPV)-related (HPV+) and HPV-unrelated (HPV−) locally advanced head and neck cancer (LAHNC). A survival benefit with cisplatin dose >200 mg/m 2 is evident for HPV− LAHNC. There was no significant survival difference in various cisplatin doses in HPV+ LAHNC overall. There was a trend towards inferior survival with cisplatin ≤200 mg/m 2 in HPV+ T4 or N3 subset.